2005
DOI: 10.1007/s00421-005-1361-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperoxia on maximal O2 uptake in exercise-induced arterial hypoxaemic subjects

Abstract: This study focuses on the effect of hyperoxia on maximal oxygen uptake VO2max and maximal power (Pmax) in subjects exhibiting exercise-induced arterial hypoxemia (EIH) at sea level. Sixteen competing male cyclists VO2max > 60 ml.min(-1).kg(-1)) performed exhaustive ramp exercise (cycle-ergometer) under normoxia and moderate hyperoxia (FIO2 = 30%). After the normoxic trial, the subjects were divided into those demonstrating EIH during exercise [arterial O2 desaturation (delta SaO2) >5%; n = 9] and those who did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…The modest increase in W max under hyperoxia found in the current study is in line with previous studies performed mostly in young athletes breathing oxygen- enriched air with various fractions of O 2 of 0.3-1.0 [11,17,18,19,20,21]. Our data extend these findings by showing a similar effect of hyperoxia on exercise performance in nonathletic - albeit relatively fit - subjects of both genders and of a broad age range (24-66 years).…”
Section: Discussionsupporting
confidence: 81%
“…The modest increase in W max under hyperoxia found in the current study is in line with previous studies performed mostly in young athletes breathing oxygen- enriched air with various fractions of O 2 of 0.3-1.0 [11,17,18,19,20,21]. Our data extend these findings by showing a similar effect of hyperoxia on exercise performance in nonathletic - albeit relatively fit - subjects of both genders and of a broad age range (24-66 years).…”
Section: Discussionsupporting
confidence: 81%
“…At SL, EIH is already known to negatively affect VO 2max [8] and subsequently exercise performance [10]. In this study at 2150 m, EIH athletes demonstrated a higher decline in VO 2max from SL than non-EIH athletes.…”
Section: Discussionmentioning
confidence: 54%
“…“EIH athletes” show a difference between rest and maximal arterial O 2 pressure (PaO 2 ) values for at least 10 mmHg and/or a delta of SaO 2 of at least 4% [9]. It is reported that EIH subsequently affects performance in response to high intensity exercise [10]. Physiopathology of EIH seems to be 1) a relative hypoventilation related to training adaptation and 2) gas exchange abnormality [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of the literature, we identified four randomized-controlled trials, which included a least eight subjects and provided data on the effect of hyperoxia vs. normoxia air on maximal exercise performance in terms of workload or V O 2 (Table A2). All revealed an increased workload of V O 2 under hyperoxia (20,42,48,68).…”
Section: Effect Of Hyperoxia On Exercise Performance In Healthy Indivmentioning
confidence: 96%